Selling and negotiation skills: A pragmatic approach - Chaudhary, Prashant (London Routledge, 2025)
This book offers a comprehensive guide to mastering essential selling and negotiation skills, giving a competitive advantage in today$1 (Bs challenging business environment. It covers a wide range of negotiation strategies, tactics, and styles that are compatible with emerging business models and technologies. With businesses adapting to shifting consumer behaviour, the book focuses on sustainable, future-ready selling and negotiation approaches. Richly illustrated with real-life examples and business cases, it makes complex concepts easy to understand.s